PENGARUH PELATIHAN KARYAWAN TERHADAP KUALITAS PELAYANAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Faisal Faisal; Murkhana Murkhana (Departemen Manajemen, Universitas Syiah Kuala, 2019)
This research aims to know the influence of training employee to service quality with organizational commitment as variables mediating on employee and patients Cut Meutia Regional General Hospital, North Aceh District, Aceh. This research method using the questionnaire as an instrument of research. Saturation Sampling and purposive sampling used as a sampling technique. Methods of analysis of the HLM (Hierarchical Linear Modeling) is used as a method of analysis to find out the influence of the variables involved. The results of this study indicate that employee training is positive and significant effect on service quality, employee training positive and significant effect on organizational commitment, organizational commitment positive and influential significantly to service quality, and employee training positive and significant effect to service quality that is mediated by organizational commitment.Keyword employee training, organizational commitment, Service quality.